The Effect of Salt Reduction and Partial Substitution of NaCl by KCl on Physicochemical, Microbiological, and Sensorial Characteristics and Consumers' Acceptability of Semi-Hard and Hard Lactose-Free Cow's Milk Cheeses - Juan, Bibiana; Trujillo, Antonio-José; Ferragut, Victoria (Frontiers in Nutrition, 2022)
Increasing consumer demand for healthier foods prompts the development of cheeses reduced in salt. The aim of his study was to assess the effect of reducing the level of sodium chloride (NaCl) and their partial substitution by potassium chloride (KCl) on the biochemical, microbiological, and sensorial characteristics and consumer's acceptability of semi-hard and hard lactose-free cow's milk cheeses. To improve the possible lower salty taste or the development of bitter taste, the addition to yeast extract, as a flavor enhancer, was also checked. Different brining times and brine conditions were tested to obtain a reduction of >25% of salt with respect to conventional cheese. Reduced-salt cheeses were elaborated by reducing half the salting time used in conventional cheeses, and a ratio of 60 Na+:40 K+ was used to reduce Na concentration in substituted cheeses. The results obtained in this study show that the reduction of salt by both methods in semi-hard and hard lactose-free cheeses could be an alternative for the production of healthier and sensorial acceptable cheeses, without significantly affecting their physicochemical characteristics. The addition of yeast extract, as a flavor enhancer, increased the free amino acids (FAAs) levels but decreased the acceptability of cheeses.